"'Eat, Pray, Love' Bullshit": Women's Empowerment through Wellness at an Elite Professional Conference. (February 2019) - Mickey, Ethel L.
Professional women's groups and conferences aim to improve women's status in the workplace through networking and the exchange of resources. This article applies a critical feminist lens to one women's conference, illustrating how the collective space paradoxically individualizes women's career experiences. Drawing upon participant observation at the Innovative Women in Business Conference, I explore how the conference's goal to connect businesswomen is replaced by a focus on women's empowerment through individual control and wellness. The conference encourages women to engage in wellness practices such as egg freezing to improve their personal market value. By focusing on strategies to "have it all, " the conference reconfigures the feminist value of empowerment to convert gender inequality to an individual affair. While most women embrace the neoliberal feminism of the conference, I find that many women attendees employ tactics to resist the wellness demands, or what one attendee refers to as "'Eat, Pray, Love' bullshit." This women-only conference represents a neoliberal, entrepreneurial intervention contributing to the (re)production of a self-regulating, feminist subject.